A Double Blind, Placebo Controlled Clinical Trial on Hospitalized Covid Patients using Informed Water - Bengston, William; Nies, Margaret (Journal of Scientific Exploration, 2023)
Two technological hurdles need to be overcome for biofield therapies to transition from fringe status to active clinical application. First, healing intention must be able to be stored, and second, it must be able to be scaled. Work on the storage problem has been done for some decades, but the scalability problem has rarely been addressed. The present study evaluates the therapeutic effect of "informed water" on West African patients entering a hospital for Covid. One hundred sixty patients were randomly assigned to either a treatment or control group. Both groups were blindly administered sublingual drops of water over the course of a week. The two water formulations given sublingually to the treatment group went through a physical device designed to capture and reproduce the healing phenomenon. The control group was administered sublingual drops of untreated water. Multiple Covid symptoms were measured daily over the course of a week. In addition, multiple PCR tests were administered. The patients receiving the informed water were blindly assessed to have significant improvements on a number of symptoms, and those patients also reported higher levels of general health and fewer positive PCR results. The data from this experiment are strongly suggestive that 1) water is a good medium for the storage of healing; 2) the therapeutically prepared water can be replicated by a physical device and is hence scalable; 3) mass-produced water can deliver a strong therapeutic effect on Covid; 4) there are no negative side effects. Future work on additional health conditions needs to be carried out.